2007
DOI: 10.5713/ajas.2007.754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inclusion of Dehydrated Food Waste Products on Taiwan Native Chicken (Taishi No. 13)

Abstract: The effect of dehydrated food waste product (DFWP) inclusion in diets of Taiwan native chickens on the growth performance, carcass traits, clinical blood chemistry and nutrient digestibility was investigated with 320 male Taishi Native Chickens (Taishi No. 13). They were randomly allocated into four levels of DFWP inclusion (0, 5, 10, or 20%) treatment. Each treatment had 80 chickens with four replicates. At 15 weeks of age, 8 chickens were selected from each group for the nutrient digestibility trial. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
3
15
1
2
Order By: Relevance
“…Protein efficiency ratio decreased with increasing ash content of meat and bone meal from 24% to 34% (Johnson and Parsons 1997). In contrast to the results of present study, Chen et al (2007) observed increased protein digestibility in chickens fed dehydrated food waste at 20% level in the diets. Digestibility of crude fiber in birds fed low EPR (high protein content) was the highest (P<0.01) compared to the other treatments at day 42.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Protein efficiency ratio decreased with increasing ash content of meat and bone meal from 24% to 34% (Johnson and Parsons 1997). In contrast to the results of present study, Chen et al (2007) observed increased protein digestibility in chickens fed dehydrated food waste at 20% level in the diets. Digestibility of crude fiber in birds fed low EPR (high protein content) was the highest (P<0.01) compared to the other treatments at day 42.…”
Section: Resultscontrasting
confidence: 99%
“…Similarly, Ratriyanto et al (2014) also observed increased crude fiber digestibility in broilers fed high-protein diets compared to low-protein diets. Chen et al (2007) reported increased crude fiber digestibility due to the inclusion of dehydrated food waste in the diet of Taiwan native chickens. Ash digestibility was lower (P<0.001) in birds fed normal and high EPR diets compared to the control diets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penambahan serat dalam pakan selain dapat mengurangi penimbunan lemak (lemak abdominal) pada ternak unggas juga dapat menurunkan konsumsi pakan. Kuo-Lung et al (2007) melaporkan bahwa penambahan selulosa sampai dengan tingkat 10,80% ke dalam ransum dapat menurunkan efisiensi pakan dan menurunkan kandungan lemak abdominal pada ayam.…”
Section: Pendahuluanunclassified
“…Bahan pakan yang diberikan antara lain adalah jagung, bungkil kedel dan padi (gabah) sebagai sumber serat. Pemanfaatan pakan yang efisien pada unggas tidak hanya dilihat dari aspek pertumbuhan dan PBB, akan tetapi juga harus dilihat dari efisiensi penggunaan tingkat protein dan energi dalam pakan untuk menghasilkan bobot hidup dan bobot karkas yang maksimal serta rendahnya kandungan lemak abdominal (Kuo-Lung et al 2007). Hasil penelitian ini memberi indikasi bahwa pemberian serat kasar sebesar 6 atau 9% dengan kandungan protein pakan 19 dan 21% masih dapat ditolerir itik untuk menghasilkan PBB yang ideal pada itik EMPp umur 12 minggu.…”
Section: Pertambahan Bobot Badan (Pbb) Itikunclassified